2010
DOI: 10.1002/esp.2084
|View full text |Cite
|
Sign up to set email alerts
|

Interpreting luminescence data from a portable OSL reader: three case studies in fluvial settings

Abstract: Optically stimulated luminescence (OSL) is a technique that has been applied from the mid-1980s, mainly for sediment dating. The OSL technique is based on sample stimulation by light to determine the luminescence signal that is stored in the crystal lattices of sediment grains after deposition, burial by later sediment and subsequent exposure to ionizing radiation from radioactive elements in the surrounding sediment. In such sediment dating, two parameters are required: the equivalent dose (i.e. the luminesce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
0
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 54 publications
(56 citation statements)
references
References 34 publications
1
53
0
2
Order By: Relevance
“…Munyigwa et al 2012, Figures 6 and 7) and, as with this study, have shown it is possible to identify stratigraphic breaks which are not necessarily discernible (e.g. Kinnard et al 2012;Muñoz-Salinas et al 2011). POSL profiling of very recent sediments, such as investigated in this study, appears to be successful and supports the findings of Muñoz-Salinas et al (2012) who successfully used PSOL data from deposits which were in the 10-500 year range.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Munyigwa et al 2012, Figures 6 and 7) and, as with this study, have shown it is possible to identify stratigraphic breaks which are not necessarily discernible (e.g. Kinnard et al 2012;Muñoz-Salinas et al 2011). POSL profiling of very recent sediments, such as investigated in this study, appears to be successful and supports the findings of Muñoz-Salinas et al (2012) who successfully used PSOL data from deposits which were in the 10-500 year range.…”
Section: Discussionsupporting
confidence: 85%
“…As shown elsewhere (e.g. Sanderson et al 2003;Kinnaird et al 2011;Muñoz-Salinas et al 2011), where more varied sediment types are profiled then correction might be of more significance. Given the IR data are generated as part of the Post IR OSL then seeing whether this is the case does not detract from the principle of rapid on site profiling.…”
Section: Discussionmentioning
confidence: 75%
“…3B and C) (Sanderson and Murphy, 2010); which has been successfully tested and used to elucidate sedimentological processes (Sanderson and Murphy, 2010;Bishop et al, 2011;Muñoz-Salinas et al, 2011).…”
Section: Methodsmentioning
confidence: 99%
“…La metodología que se aplicó para la recolección de las muestras en campo siguió los protocolos propuestos por Muñoz-Salinas et al (2011). El protocolo conlleva la cobertura del perfil en trabajo de campo con una tela oscura para proceder a la limpieza del material superficial en el afloramiento y así remover todos aquellos granos expuestos a la luz solar.…”
Section: Metodologíaunclassified
“…La interpretación de las señales de luminiscencia en sedimentos, sin proceder a su datación, ha sido propuesta más recientemente (Sanderson y Murphy, 2010;Muñoz-Salinas et al, 2011;Munyikwa et al, 2012) y se ha puesto de manifiesto que el uso de dichas señales es una herramienta útil en el estudio de sedimentos fluviales para dilucidar los mecanismos de transporte de sedimentos . Ejemplo del uso de este enfoque es el trabajo de Sanderson y Murphy (2010), en el cual se analizan las señales luminosas que provienen de muestras de sedimento extraídas de un perfil vertical que corta los depósitos de un enclave arqueológico en Petrilli, en la región de la Puglia, Italia.…”
Section: Introductionunclassified